Targeted drug delivery system for ovarian cancer microenvironment: Improving the effects of immunotherapy - Peng, Hongling; He, Xiang; Wang, Qiao (Frontiers in Immunology, 2022)
The immunotherapies showed modest benefit in the current clinical trials for ovarian cancer. The tumor microenvironment (TME) in an immunosuppresive phenotype contributes to this ‘failure’ of the immunotherapy in ovarian cancer. Many stromal cell types in the TME (e.g. tumor-associated macrophages and fibroblasts) are identified of plasticity in anti- and pro-tumor activities, and are responsible for suppressing the anti-tumor immune response. Thus, the TME is a very valuable target for adjuvant interventions to improve the effects of immunotherapy. The current strategies targeting the TME include: 1) eliminating the immunosuppressive cells or transforming them into immunostimulatory phenotypes; 2) inhibiting the immunosuppressive or pro-tumor production of them. Most of the effective agents acting on the above strategies are gene materials (e.g. cDNA, mRNA, or microRNA), proteins, or other small molecules (e.g. peptides), which are limited in target and instability. Various formulations of drug delivery system (DDS) are designed to realize the controlled release and targeting delivery of these agents to the tumor sites. Nanoparticles and liposomes are the frequently exploited materials. Based on current evidences from preclinical and clinical studies, the future of DDS is promising in cancer immunotherapy, since the combination of agents with DDS showed increased efficacy and decreased toxicities compared with free agents. In the future, more efforts are needed to further identify the hallmarks and biomarkers in the ovarian TME, which is crucial for engineering more effective, safe, and personalized DDSs.